Industry of Children’s Toys and Trends on Toy Market in the EU and Russia - S. L. Kalachev; I. A. Makhotina (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The article shows commodity expertise aspects of children’s goods market, in particular children’s toys. Demographic and economic factors are called as major ones for the development of global and Russian market of children’s goods. The place of toys in the product-range of children’s goods was identified, s well as their social role. The authors provide such figures as global sales volume of children’s goods, import and export of toys in the Russian Federation. They research key categories of toys, structure of their sales, analyze key global trends of production and consumption of toys, trends typical of the EU and Russia. Promising lines of production and selling toys in the EU and Russia were highlighted and specific features of Russian state policy in respect of children’s goods manufacturers were presented. Preconditions for the development of Russia industry of children’s goods were discussed.